Possibility of acute ascending aortic dissection treatment with moderate hypothermic circulatory arrest - V. V. Boiko; O. V. Buchnieva; Y. V. Shafer; Y. V. Pisklova; Y. V. Bogun; O. S. Krylova; Y. D. Kriuchkov; O. I. Tkach (Ukrainian Journal of Cardiovascular Surgery, 2018)
The issues considering the type of surgical treatment for acute aortic dissection, the temperature mode and the use of circulatory arrest during surgeries on thoracic aorta are of current importance today. It is undisputed that the risks of postoperative complications decrease among patients who underwent surgery without circulatory arrest. Surgical risks among patients with acute aortic dissections is mostly due to the necessity of deep hypothermia for circulatory arrest. In ST “Zaycev V. T. Institute of General and Urgent Surgery AMS of Ukraine” 21 patients with acute ascending aortic dissections underwent surgery using moderate hypothermic circulatory arrest.